Enhanced Transmission of 0.64 Tbps in DWDM-RoF Technique Along 180 km Transmission Distance for 5G Mobile Communication (Journal of Engineering, 2025)
This paper introduces enhanced filtered channels in the suggested design of the optical communication system formed for 5G mobile communication over optical fiber. The main goal is to overcome the limited bandwidth of radio wave systems and to enable high-data-rate transmission. The dense wavelength division multiplexing based on the radio-over-fiber (DWDM-RoF) system has succeeded in satisfying a high data rate of 0.64 Tbps by a multichannel filtered system through a 180 km distance within the C-Band through a multichannel filtered approach. The design includes 64 filtered channels with an optimized bandpass filter (BPF), making unprecedented channel convergence possible. The system transmits at low power 0 dBm (1.0 mW) over single-mode fiber (SMF) 180 km and uses the dispersion compensation fiber (DCF) 18 km. It converts light to electrical signals and is filtered by a low pass filter at 0.75 of the bit rate (B) set at 10 Gbps. The model is applied in Optiwave 7.0 software the results are the figures showed the overwhelming success enhanced by the opened-eye diagram, the value of the Q factor is 6.72, and the BER is 7.1E-12 across 180 km of the center frequency =193.13 THz (1553.5 nm) for 50 GHz spacing between channels.